Aggregation-induced phosphorescence sensitization in two heptanuclear and decanuclear gold–silver sandwich clusters. Issue 2 (12th November 2020) - Lu, Zhou; Yang, Yu-Jie; Ni, Wen-Xiu; Li, Mian; Zhao, Yifang; Huang, Yong-Liang; Luo, Dong; Wang, Xiaoping; Omary, Mohammad A.; Li, Dan
Abstract : The strategy of aggregation-induced emission enhancement (AIEE) has been proven to be efficient in wide areas and has recently been adopted in the field of metal nanoclusters. Abstract : The strategy of aggregation-induced emission enhancement (AIEE) has been proven to be efficient in wide areas and has recently been adopted in the field of metal nanoclusters. However, the relationship between atomically precise clusters and AIEE is still unclear. Herein, we have successfully obtained two few-atom heterometallic gold–silver hepta-/decanuclear clusters, denoted Au6 Ag and Au9 Ag, and determined their structures by X-ray diffraction and mass spectrometry. The nature of the Au I ⋯Ag I interactions thereof is demonstrated through energy decomposition analysis to be far-beyond typical closed-shell metal–metal interaction dominated by dispersion interaction. Furthermore, a positive correlation has been established between the particle size of the nanoaggregates and the photoluminescence quantum yield for Au6 Ag, manifesting AIEE control upon varying the stoichiometric ratio of Au : Ag in atomically-precise clusters.